Relationships between seat properties and human subject kinematics in rear impact tests - Welcher, Judson B; Szabo, Thomas J (Accident analysis and prevention, 2001)
The mitigation of whiplash associated disorders (WAD) has received increased priority in the last 10 years. Although the exact mechanism(s) for WAD causation have not been established, several have been proposed and it is likely the mechanism(s) are associated with the kinematics of the head relative to the torso. It follows that automotive seat designs that address reductions in certain head–torso kinematics may lead to a reduction in WAD potential. Seat properties that may have an effect on head–neck kinematics include geometry, stiffness and energy absorption. This study evaluated the performance of five seats with varying properties, including the new Volvo ‘WHIPS’ seat. Seat properties such as geometry relative to the occupant's head, dynamic and static stiffness, and energy absorption were determined via component testing. A new prototype dynamic seat test, which used a pendulum and seat back pan, was evaluated. Human subject impact tests were conducted using three occupants in rear impacts with velocity changes of 4 and 8 km/h. Potentially relevant occupant kinematic parameters were identified, and then correlated with seat properties in an attempt to determine any relative influence of seat properties on potential WAD mechanisms. Two higher velocity human subject tests using the Volvo Whiplash Injury Protection System (WHIPS) seat were also conducted. Vertical and horizontal head to head restraint distances were found to be most influential on occupant head–neck kinematics. Horizontal and vertical head to head restraint offsets were significantly correlated with rearward translational motion of the head center of gravity relative to the upper torso across all occupants. Rearward offset was also significantly correlated with rearward rotation of the head relative to upper torso, while vertical offset was significantly correlated with head acceleration relative to the upper torso during the flexion phase of the impact. Seat constitutive properties such as stiffness and energy absorption were not significantly correlated with occupant head–neck kinematics. The new dynamic seat test posed problems in data interpretation, and suggestions for improvement are made. The Volvo ‘WHIPS’ seat proved to be very effective in reducing many potential WAD associated head–neck kinematics. The two increased severity impacts activated the additional protective energy absorption elements in the seat, and no injuries were sustained by the occupants.